Sustainable utilization of desalination concentrate - ElBarmelgy, Amira Hesham (AUC Knowledge Fountain, 2019)
Lack of water availability is a global crisis. Many arid countries are turning to desalination technologies in order to fulfill their water needs. Hypersaline water, brine, is the byproduct of desalination and can be dangerous to the environment if disposed of in an unsustainable manner. Research surrounding brine management focuses on improved methods of direct disposal, strategies of volume minimization, and reuse strategies. However, the mentioned brine management methods revolve around chemical and mechanical techniques requiring high technological skills, know-how and energy. This thesis aims to find biological solutions that use brine, with minimum resources, in low-cost, low-energy conditions to generate economic value and to minimize the negative effects of brine by attempting to reducing brine salinity. After conducting a thorough literature review, two possible organisms, with the potential of living in brine, algae and Artemia were selected. Different algae species are able to withstand high saline environments and uptake minerals from concentrated solutions; thus decreasing its overall salinity. Artemia sp. thrives in high saline conditions producing cysts of large economic value. This thesis aims to demonstrate that Artemia can live in brine and is a viable method for revenue generation and that the algae species Nannochloropsis sp. can also be adapted to live in brine and uptake nutrients, somewhat decreasing the salinity of brine. The Artemia and algae biomass can be sold, generating additional economic benefits and minimizing the cost of such a system, thus allowing for an economically, socially and environmentally safe way to utilize desalination waste. Marine microalga Nannochloropsis sp. was tested for its salt stress tolerance and salt accumulation capability in mediums of sea salt and brine with different concentrations and nutrients. In sea salt experiments, the alga grew best in salinity 80,000 mg.l-1 with F/2 nutrients where it reached an increase of 4-fold. In brine test BH with F/2 nutrients, excluding the vitamin stock solution and substituting NaNO3 with urea, the alga was able to reach a higher growth of 5-fold. Salt accumulation was minimal and thus will not decrease the TDS of brine. Nevertheless, the optimum conditions for growth of Nannochloropsis sp. in brine were identified, the biomass may be utilized for biofuel production, to generate economic value. Artemia experiments demonstrated the organism’s ability to survive in brine. The Artemia was able to survive for two months in a medium of 100% brine, indicating that a larger brine project may be conducted using this organism to generate economic value.